2014
DOI: 10.1093/mnras/stu1851
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength observations of the black hole transient Swift J1745−26 during the outburst decay

Abstract: We characterized the broad-band X-ray spectra of Swift J1745−26 during the decay of the 2013 outburst using INTEGRAL ISGRI, JEM-X and Swift XRT. The X-ray evolution is compared to the evolution in optical and radio. We fit the Xray spectra with phenomenological and Comptonization models. We discuss possible scenarios for the physical origin of a ∼50 day flare observed both in optical and Xrays ∼170 days after the peak of the outburst. We conclude that it is a result of enhanced mass accretion in response to an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…This would suggest that the overall mass-transfer rate during the outburst is not the only parameter involved in the "failed" state transition behavior or that the limit is higher than what Tetarenko et al (2016) thought. However, even though the most widely accepted distance of Swift J1745-26 is 7 kpc (Curran et al 2014;Kalemci et al 2014), this value is poorly constrained (Muñoz-Darias et al 2013). Thus, if we assume a distance lower than ∼4 kpc, even the BHT Swift J1745-26 would fall within the proposed upper limit of 0.11 L Edd .…”
Section: Discussionmentioning
confidence: 88%
“…This would suggest that the overall mass-transfer rate during the outburst is not the only parameter involved in the "failed" state transition behavior or that the limit is higher than what Tetarenko et al (2016) thought. However, even though the most widely accepted distance of Swift J1745-26 is 7 kpc (Curran et al 2014;Kalemci et al 2014), this value is poorly constrained (Muñoz-Darias et al 2013). Thus, if we assume a distance lower than ∼4 kpc, even the BHT Swift J1745-26 would fall within the proposed upper limit of 0.11 L Edd .…”
Section: Discussionmentioning
confidence: 88%
“…from E to F On the return branch from soft to hard, as we have seen above the reverse track is followed, through the SIMS and the HIMS, on a time scale compa-rable to that of the upper track. Observations of several transitions from multiple systems have shown that the compact radio jet is re-formed not in correspondence to the SIMS-HIMS transition, but when the system has reached the LHS, a delay of several days (see [74,73] and references therein. At the time of radio re-appearance, secondary maxima have been seen in the optical-infrared band, which have been attributed to direct jet emission, although alternative models exist [74].…”
Section: Radio Jetsmentioning
confidence: 99%
“…1. X-rays heating the companion, increasing the mass accretion rate (outburst 'echos'; see Lasota 2001;Dubus et al 2001;Kalemci et al 2014, and references therein), 2. synchrotron emission from the reactivation of the jet in the hard state decay (e.g. Kalemci et al 2013),…”
Section: Introductionmentioning
confidence: 99%